2015
DOI: 10.1002/14651858.cd007399.pub2
|View full text |Cite
|
Sign up to set email alerts
|

The use of propofol for procedural sedation in emergency departments

Abstract: No firm conclusions can be drawn concerning the comparative effects of administering intravenous propofol, with or without an adjunctive analgesic agent, with alternative interventions in participants undergoing PS in the ED setting on adverse effects (including pain at the injection site) and participant satisfaction. The review was limited because no two included studies employed the same comparator interventions, and because the number of participants in eight of the included studies were small (fewer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…From 2,882 unique references, 14 completed systematic reviews were included (Figure , Table ). Three protocols for in‐process reviews were identified on propofol and midazolam for procedural sedation and structured sedation programs in acute care settings; since the protocols provide no data they are not included in this review. The number of primary studies across all reviews was 435; however, not all studies were relevant to our topic (e.g., some included both pediatric and adult populations or settings other than the ED).…”
Section: Resultsmentioning
confidence: 99%
“…From 2,882 unique references, 14 completed systematic reviews were included (Figure , Table ). Three protocols for in‐process reviews were identified on propofol and midazolam for procedural sedation and structured sedation programs in acute care settings; since the protocols provide no data they are not included in this review. The number of primary studies across all reviews was 435; however, not all studies were relevant to our topic (e.g., some included both pediatric and adult populations or settings other than the ED).…”
Section: Resultsmentioning
confidence: 99%
“…149 Some upcoming evidence exists on intranasal drug administration during PSA, for example for dexmedetomidine. 155 Propofol remains the most common sedative drug, [156][157][158][159][160][161][162] mainly for its short onset time (30 to 60 s), predictable duration of action and short context-sensitive half-time. It induces a dose-dependent amnesia and sedation, leading to unconsciousness and general anaesthesia at higher concentrations.…”
Section: H Location and Environment For Procedural Sedation And Analg...mentioning
confidence: 99%
“…However, insufficient information was available regarding the total number of anesthetized patients, thus it was impossible to evaluate the incidence of these side effects. In 2015, a Cochrane systematic review of sedation administered in emergency departments was unable to draw a conclusion regarding the effectiveness and safety of the different types of existing sedation due to the low number of sufficient quality clinical trials available [ 17 ].…”
Section: Discussionmentioning
confidence: 99%